2019
DOI: 10.2807/1560-7917.es.2019.24.25.1900340
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plasmid-mediated tigecycline-resistant gene tet(X4) in Escherichia coli from pork, Sichuan and Shandong Provinces, China, February 2019

Abstract: The plasmid-mediated high-level tigecycline resistance gene, tet (X4), was detected in seven Escherichia coli isolates from pork in two Chinese provinces. Two isolates belonged to the epidemic spreading sequence type ST101. Tet (X4) was adjacent to IS Vsa3 and concurrent with floR in all seven isolates. In addition to IncFIB, the replicon IncFII was found to be linked to tet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 9 publications
4
58
0
1
Order By: Relevance
“…The data shown here represents a timely follow-up study in response to the newly-identification of tet (X4) [tet(X5)] [5,6,19]. It provides an efficient and powerful approach to detect the prevalence of tet(X) family of variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data shown here represents a timely follow-up study in response to the newly-identification of tet (X4) [tet(X5)] [5,6,19]. It provides an efficient and powerful approach to detect the prevalence of tet(X) family of variants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we developed an efficient multiplex PCR method to detect the family of mcr-like genes [20]. As of reporting our method, tet(X4) is only detected in non-human E. coli isolates [5,6,19], whereas tet(X5) is exclusively present in Acinetobacter baumannii [5]. The current situation of tet(X4) [tet(X5)] epidemiology in China is generally consistent with our observation with the multiplex PCR method we developed (Table 2 and Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The two tet(X6)-bearing MDR regions differed by virD2-floR-ISCR2, which was a potential mobile segment (Doublet et al, 2005). ISCR2 is the major mobile element associated with tet(X3), tet(X4), and tet(X5) (Bai et al, 2019;He et al, 2019;Sun et al, 2019;Li et al, 2020a). Recently, three reports demonstrated tet(X6) could be embedded in ICEs FIGURE 3 | The phylogenetic tree of Tet(X) variants.…”
Section: Characterization Of Proteus Cibariusmentioning
confidence: 99%
“…In recent years, the clinical use of tigecycline has resulted in the global emergence of resistance. Although three tet(X) variants, tet(X), tet(X1), and tet(X2), have been reported in Bacteroides, Enterobacteriaceae, and Acinetobacter, no experimental verification showed that these tet(X) genes could be horizontally transferred and mediate high-level resistance to tigecycline (9-12) until a report describing two novel plasmidborne high-level tigecycline resistance genes, tet(X3) and tet(X4), in A. baumannii and E. coli (3,13). The acquisition of tet(X3) or tet(X4) by pathogenic species in a clinical setting may render tigecycline ineffective, severely limiting treatment options.…”
mentioning
confidence: 99%